2012
DOI: 10.4103/2249-4863.94448
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices of paracetamol administration among caregivers of pediatric age group patients

Abstract: Introduction:Paracetamol is a widely used over the counter drug for pyrexia and mild to moderate pain in all age groups.Objective:To assess the knowledge and practices of paracetamol administration among caregivers of the pediatric age group patients attending the university family practice.Materials and Methods:A clinic-based descriptive cross-sectional survey was carried out among clients attending the family practice of the Faculty of Medicine, University of Kelaniya, Sri Lanka using pretested interviewer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 4 publications
3
23
1
Order By: Relevance
“…The current study explored the knowledge and practices of administration of paracetamol to children. Confirming with the available literature, most of the parents incorrectly believed that children's paracetamol syrup is more concentrated than infant drops (3,9) which can lead to either overdose or underdose. Further, the situation is complicated with the availability of number of brands with varying concentrations.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The current study explored the knowledge and practices of administration of paracetamol to children. Confirming with the available literature, most of the parents incorrectly believed that children's paracetamol syrup is more concentrated than infant drops (3,9) which can lead to either overdose or underdose. Further, the situation is complicated with the availability of number of brands with varying concentrations.…”
Section: Discussionmentioning
confidence: 86%
“…The questionnaire was developed based on published literature (9). It consisted of four sections to cover demographic characteristics, knowledge of parents on calculation and measuring the dose, frequency of administration, available forms etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were obtained from a study conducted in Srilanka which reported the significant association between pattern of administration and dosage quantity (p=0.03 and X 2 =3.183). 3 Only 30 (19.3%) of the subjects were aware of the side effects of paracetamol overdose and significant number 37 (23.7%) did not agree with the statement that paracetamol overdose causes liver toxicity. This might be because of the misconceptions like it is widely used drug so it is weak and less risky than the other drugs.…”
Section: Discussionmentioning
confidence: 98%
“…This is supported by the fact proved by many studies that paracetamol is the most commonly used antipyretic and analgesic in children. [1][2][3]6,8 The administration of paracetamol by self medication 90 (57.6%) is far more than by doctor's prescription 66 (42.3% The finding that 39 (25%) administered above the recommended dose is supported by a study from Sri Lanka which reported that 43% subjects gave supratherapeutic dose of paracetamol. 3 Most of the subjects 57% (below recommended dose) and 54% (above recommended dose) administered same amount of ≤10 mg/kg/dose less and more than the recommended dose respectively.…”
Section: Discussionmentioning
confidence: 99%